PELATIHAN MANAGEMEN KEUANGAN BAGI MITRA BINAAN BAZNAS MICROFINANCE DESA (BMD) GUNUNGSARI TAHUN 2024: Financial Management Training For Gunungsari Village Baznas Microfinance (BMD) Partners Year 2024 - M. Zainuddin; Karmana, I Wayan; ., Nofisulastri; Zulaifi, Reza; Mustakim, Ichwanul; Gunawan, I Made Sony; Samsuri, Taufik; Hariadi, Ahmad; Yani, Ahmad (Yayasan Al-Amin Qalbu, 2024)
The obstacle to the assistance provided is that MSME actors still do not have awareness and understanding in managing the financial management of business results, which means that the business they run is not able to develop optimally. Seeing conditions like this, in this community service, we raised the title